PENGARUH DEBT TO EQUITY RATIO, DEBT TO ASSET RATIO DAN CURRENT RATIO TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BEI - Ardella Anggraini Simanjuntak; Hamida Sari Siregar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to determine the partial and simultaneous influence of Debt to Equity Ratio, Debt to Asset Ratio and Current Ratio on Financial Performance in Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange. The number of population samples of 48 companies and samples of 15 companies multiplied by 3 observation years 2022-2024 to 45 samples. However, from the 40 samples, 3 samples were found from outlier observations so that they were eliminated as samples, then data was obtained as many as 42 samples. Data analysis using Multiple Linear Regression. The results of the t-test, partially the Debt to Equity Ratio had a positive effect on financial performance with a tcal value of 2.331 > ttable 2.022 and a significance of 0.025 < 0.05. Debt to Asset Ratio partially has a negative effect on Financial Performance with a value of -tcal (-3.120) < -ttable (-2.022) with a significance value of 0.003 < 0.05. Meanwhile, the Current Ratio has a negative effect on financial performance with a value of -tcal (-3.498) < -ttable (-2.022) with a significance value of 0.001 < 0.05. Meanwhile, the results of the F Test simultaneously show that the Debt to Equity Ratio, Debt to Asset Ratio, and Current Ratio variables have an effect on Financial Performance with a Calculation value of 6.768 > 2.85 F and a significance value of 0.001 < 0.005. The R2 test, the Adjusted R Square value produced a value of 0.297, meaning that the correlation of all independent variables consisting of Debt to Equity Ratio, Debt to Asset Ratio, and Current Ratio to the dependent variable, namely financial performance, was 29.7% while the remaining 70.3% was influenced by other factors that were not included in this research model. Keywords: Debt to Equity Ratio, Debt To Equity Ratio, Current Ratio, Financial Performance   Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh parsial dan simultan dari Debt to Equity Ratio, Debt to Asset Ratio dan Current Ratio terhadap Kinerja Keuangan pada Perusahaan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia. Jumlah sampel penduduk 48 perusahaan dan sampel 15 perusahaan dikalikan 3 tahun observasi 2022-2024 menjadi 45 sampel. Namun, dari 40 sampel tersebut, ditemukan 3 sampel dari pengamatan outlier  sehingga dieliminasi sebagai sampel, kemudian diperoleh data sebanyak 42 sampel. Analisis data menggunakan Regresi Linier Berganda. Hasil uji t, sebagian Debt to Equity Ratio berpengaruh positif terhadap kinerja keuangan dengan nilai thitung 2,331 > ttabel 2,022 dan signifikansi 0,025 < 0,05. Debt to Asset Ratio berpengaruh negatif terhadap Kinerja Keuangan dengan nilai -thitung (-3,120) < -ttable (-2,022) dengan nilai signifikansi 0,003 < 0,05. Sementara itu, Current Ratio berpengaruh negatif terhadap kinerja keuangan dengan nilai -thitung (-3,498) < -ttable (-2,022) dengan nilai signifikansi 0,001 < 0,05. Sementara itu, hasil Uji F secara simultan menunjukkan bahwa  variabel Debt to Equity Ratio, Debt to Asset Ratio, dan Current Ratio  berpengaruh terhadap Kinerja Keuangan dengan nilai Perhitungan 6,768 > 2,85 F dan nilai signifikansi 0,001 < 0,005. Uji R2,  nilai R Square yang  Disesuaikan menghasilkan nilai 0,297, artinya korelasi seluruh variabel independen yang terdiri dari Debt to Equity Ratio, Debt to Asset Ratio, dan Current Ratio terhadap variabel dependen yaitu kinerja keuangan sebesar 29,7% sedangkan sisanya 70,3% dipengaruhi oleh faktor lain yang tidak termasuk dalam model penelitian ini. Kata kunci: Rasio Utang Terhadap Ekuitas, Rasio Utang Terhadap Ekuitas, Rasio Lancar, Kinerja Keuangan